Preparation method of quantum dot material, quantum dot material and optical device
The zinc sulfide quantum dot material was prepared by a two-step method of thermal synthesis, which solved the problem of poor characteristic absorption in the 280-310nm band in the prior art, and achieved good absorption characteristic peaks and suitable optical equipment.
Patent Information
- Application Number
- CN202411938858.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-04-01
Smart Images

Figure CN119736080A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of materials, and specifically relates to a nano material with specific optical properties and a preparation method thereof, and more specifically, to a quantum dot material with specific optical characteristics and a preparation method thereof. Background Art
[0002] As a new generation of semiconductor nanomaterials, quantum dots have the properties of wide excitation spectrum, narrow fluorescence half-width, and high photochemical stability. They have broad application value in biomedicine, semiconductor optoelectronic devices, analytical chemistry, solar cells, etc.
[0003] Zinc sulfide (ZnS) is a wide bandgap semiconductor material. The bandgap width of zinc sulfide (ZnS) at room temperature is 3.6eV (cubic sphalerite) and 3.7eV (hexagonal wurtzite). Through the quantum size effect, its bandgap can be adjusted to the deep ultraviolet range. Moreover, ZnS does not contain heavy metals and is more environmentally friendly. Therefore, ZnS quantum dots are very ideal wide bandgap materials.
[0004] The excellent performance of zinc sulfide has attracted more and more attention from material scientists. People have been exploring good synthesis methods to stabilize particles and control the size of particles from a microscopic perspective. With the continuous deepening of research work, it is hoped to find low-dimensional zinc sulfide materials with uniform scale and shape and excellent optical and electrical properties. The optical absorption characteristics of existing zinc sulfide (ZnS) quantum dots are mainly concentrated in 230-280nm, and there are certain difficulties in material preparation and particle size control in the range of 280-310nm.
[0005] In addition, as a miniature spectrometer, quantum dot spectrometers have shown strong portability and accuracy in many aspects. Quantum dot spectrometers have detection capabilities in the visible region, near ultraviolet region, and near infrared region, but have insufficient detection capabilities in the above-mentioned ultraviolet region of 280-310nm. Therefore, it is necessary to improve the existing preparation method of zinc sulfide quantum dots to meet the preparation requirements of absorption quantum dot materials in a wider ultraviolet region.
[0006] However, the existing preparation technology of zinc sulfide (ZnS) quantum dots is difficult to achieve the ideal state. One of the reasons is that most methods are prepared in water phase, and the size and morphology of the obtained quantum dots are difficult to control. Usually, particles of tens or hundreds of nanometers are obtained. Therefore, such particles have extremely poor redispersibility in solvents, which seriously limits their application. Another reason is that even in the method of preparing oil-soluble quantum dots, there is a problem of poor size control. For example, it is difficult to obtain an absorption wavelength less than 260nm, and it is also difficult to obtain a material with obvious characteristic absorption at 280-310nm.
[0007] Reference 1 discloses an oil-soluble zinc sulfide quantum dot and a preparation method thereof. The oil-soluble zinc sulfide quantum dots provided by the reference have a particle size less than 2 nm and an absorption peak range of 250 to 280 nm. However, the examples show that the absorption peak of the quantum dots synthesized by the method is concentrated at 260 to 280 nm.
[0008] Reference 2 discloses a method for synthesizing zinc sulfide quantum dots using oleylamine, which comprises first adding zinc nitrate dihydrate into an oleylamine solvent under stirring, adding sulfur powder after the zinc salt is completely dissolved, and reacting at 120 to 240°C. After the reaction is completed, the mixture is washed and separated with ethanol, and finally dispersed in an organic solvent. The final quantum dot material has a size between 2 and 4 nm.
[0009] Reference document 3 discloses a method for preparing a ZnS quantum dot material and a quantum dot material, the method comprising: a step of preparing a quantum dot solution, the solution comprising an organic solvent and ZnS quantum dot particles dissolved in the organic solution, and the surface of the ZnS quantum dot particles having a first ligand compound; a step of injecting a second ligand compound, adjusting the temperature of the quantum dot solution to T, and injecting a second ligand compound comprising an aliphatic primary amine into the quantum dot solution; a separation step to obtain product quantum dot particles; wherein, in the step of injecting the second ligand compound, the temperature T is 45 to 210°C, and the temperature T is adjusted so that the absorption wavelength of the product quantum dot particles is adjusted in the range of 230 to 300 nm. Although the reference 3 mentioned in the scheme that "the light absorption peak wavelength of the product quantum dot particles is adjusted in the range of 230 to 300 nm" by adjusting the ligand and temperature, it has been found in continuous industrial practice that although the reference 3 can also provide zinc sulfide quantum dot materials with absorption characteristics in the near-ultraviolet region, its focus is on the absorption problem of light in the 230 to 250 nm band. For the 250 to 300 nm band, especially for the 280 to 300 nm band, the absorption peak shape of the quantum dot material directly provided by its method cannot be said to be satisfactory. At the same time, there is a phenomenon of too wide half-peak width, and this problem is more obvious as it approaches the 300 nm band.
[0010] It can be seen that the prior art has explored to a certain extent the synthesis of oily quantum dot materials with different ultraviolet absorption properties, especially zinc sulfide quantum dot materials, but there is still room for further improvement and exploration in the preparation of quantum dot materials that are more suitable for spectrometers and have excellent ultraviolet absorption properties in a specific wavelength region, especially the adjustable preparation of zinc sulfide quantum dot materials with the required absorption wavelength and good peak shape.
[0011] References:
[0012] Reference 1: CN108485648A
[0013] Reference 2: CN102030360A
[0014] Reference 3: CN117106442A Summary of the invention
[0015] Problem that the invention aims to solve
[0016] As mentioned above, for an ideal zinc sulfide quantum dot material, the material is required to have a well-shaped absorption characteristic peak within the detection absorption wavelength range, for example, the peak shape is relatively regular and has a suitable half-peak width.
[0017] However, based on the above requirements, there are currently the following main problems with such zinc sulfide quantum dot materials: one is that it is difficult to prepare materials with good absorption characteristic peaks for deep ultraviolet light, such as light with a wavelength below 250nm, especially for light in the 230-250nm band; the other is that for the near-ultraviolet region, such as the absorption of light with a wavelength of 280-310nm, the existing process is also difficult to provide zinc sulfide quantum dot materials with absorption characteristic peaks with good morphology.
[0018] Further, as mentioned above, reference 3 provides a zinc sulfide quantum dot material that is particularly effective for deep ultraviolet absorption, but its focus is on the absorption problem of light in the 230-250nm band, and for the 250-300nm band, especially for the 280-300nm band, the absorption peak shape of the quantum dot material directly provided by its method cannot be said to be satisfactory, and the half-peak width is too wide, and this problem is more obvious when it is closer to the 300nm band. Therefore, there is still a need for further improvement in the preparation of quantum dot materials with near-ultraviolet absorption characteristics that meet the needs.
[0019] In view of the above-mentioned situation of the prior art, the present invention mainly provides an improved preparation method of zinc sulfide quantum dots and zinc sulfide quantum dot materials. The method is based on the thermal synthesis method and is obtained through a two-step method, namely, a seed synthesis step-a secondary growth step to obtain a zinc sulfide quantum dot material having a characteristic ultraviolet absorption peak with a wavelength of 235 to 310 nm. By controlling the ultraviolet absorption characteristics of the seed particles during the synthesis process, the temperature and method in the two thermal syntheses, a zinc sulfide quantum dot material with a good characteristic absorption peak shape, a position of 235 to 310 nm, and adjustable is obtained. Moreover, the material, even in the band near 300 nm, has a characteristic absorption peak with a good peak shape sufficient to meet the needs of optical equipment (such as a spectrometer or a filter device, etc.).
[0020] Furthermore, the present invention also provides an optical device, preferably a spectrometer or a filter device, in which the zinc sulfide quantum dot material of the present invention is used or included.
[0021] Solutions for solving problems
[0022] It has been found that the above technical problems can be solved by implementing the following technical solutions:
[0023] [1]. The present invention first provides a method for preparing zinc sulfide quantum dot materials, which is a method for preparing oily quantum dots based on a thermal synthesis method, wherein the method comprises:
[0024] The steps of seed synthesis and the steps of secondary growth,
[0025] in,
[0026] In the seed synthesis step, zinc sulfide quantum dot seed particles are obtained through a first thermal synthesis step and a purification step, and the zinc sulfide quantum dot seed particles have an ultraviolet absorption characteristic peak with a wavelength of 230 to 280 nm; the purification step is to purify the obtained zinc sulfide quantum dot seeds after the first thermal synthesis step is completed to obtain the zinc sulfide quantum dot seed particles;
[0027] In the secondary growth step, the zinc sulfide quantum dot material is obtained through a second thermal synthesis step, and the temperature T2 of the second thermal synthesis step is above 120°C. The second thermal synthesis step includes mixing a sulfur source with a zinc precursor solution containing the zinc sulfide quantum dot seed particles. The absorption characteristic peak corresponding wavelength of the zinc sulfide quantum dot material prepared by the second growth step is increased by 1 to 80 nm compared with the absorption characteristic peak corresponding wavelength of the zinc sulfide quantum dot seed particles.
[0028] [2] The method according to [1], wherein in the seed synthesis step, the first thermal synthesis step comprises:
[0029] The sulfur source is mixed with the zinc precursor solution at a temperature T1 of 50 to 95°C.
[0030] [3] The method according to [2], wherein in the first thermal synthesis step, the sulfur source is used in the form of a solution.
[0031] [4] The method according to any one of [1] to [3], wherein the surface of the zinc sulfide quantum dot seed particles includes aliphatic carboxylic acid ligands.
[0032] [5] The method according to any one of [1] to [4], wherein the temperature T2 of the second thermal synthesis step is 30°C to 200°C higher than T1, and T2 is 120°C or higher.
[0033] [6] The method according to any one of [1] to [5], wherein, in the secondary growth step, the temperature of the zinc precursor solution is adjusted to T2 and then the zinc sulfide quantum dot seed particles are injected therein to form a zinc precursor solution containing the zinc sulfide quantum dot seed particles.
[0034] [7]. The method according to any one of [1] to [6], wherein in the second thermal synthesis step, a sulfur source is gradually injected into the zinc precursor solution containing the zinc sulfide quantum dot seed particles to control the position of the characteristic peak of ultraviolet absorption of the zinc sulfide quantum dot material finally obtained. Optionally, the zinc precursor solution can be supplemented during the injection of the sulfur source.
[0035] [8]. Furthermore, the present invention also provides a zinc sulfide quantum dot material prepared by the method described in any one of [1] to [6], wherein the zinc sulfide quantum dot material has an ultraviolet absorption characteristic peak with a wavelength of 280 to 310 nm; the half-peak width of the ultraviolet absorption characteristic peak is less than 25 nm;
[0036] The surface of the zinc sulfide quantum dot material has aliphatic carboxylic acid ligands with 10 to 30 carbon atoms.
[0037] [9]. Furthermore, the present invention also provides an optical device, wherein the optical device uses or contains the zinc sulfide quantum dot material obtained according to any one of the methods [1] to [7] or the zinc sulfide quantum dot material according to [8].
[0038]
[10] The optical device according to [9], which is a spectrometer or a filtering device.
[0039] Effects of the Invention
[0040] By implementing the above technical solution, the present invention can achieve the following technical effects:
[0041] 1) Through the seed synthesis-secondary growth steps, combined with the reaction temperature, the wavelength corresponding to the ultraviolet absorption characteristic peak of the zinc sulfide quantum dot material can be increased by 1 to 80 nm based on the wavelength corresponding to the absorption characteristic peak of the zinc sulfide quantum dot seed particles, thereby obtaining a zinc sulfide quantum dot material with an ultraviolet absorption characteristic peak wavelength of 231 to 310 nm that was previously difficult to obtain, and in particular, a zinc sulfide quantum dot material with an ultraviolet absorption characteristic peak wavelength of 280 to 310 nm that was previously difficult to obtain can be obtained;
[0042] 2) In particular, for the zinc sulfide quantum dot material of the present invention whose ultraviolet absorption characteristic peak wavelength is 280 to 310 nm, within this wavelength range, it has a peak shape and half-peak width suitable for a (micro) spectrometer or filtering device, thereby giving the spectrometer the function of accurately working within the wavelength range of 280 to 310 nm.
[0043] 3) The synthesis process of the zinc sulfide quantum dot material of the present invention is relatively simple and easy to control, which is beneficial for industrialized stable and large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] Figure 1 to Figure 7 The ultraviolet absorption characteristics of the quantum dot materials obtained in Examples 1 to 7 of the present invention are respectively;
[0045] Figure 8 In Comparative Example 1 of the present invention, the zinc sulfide quantum dot seed particles are not purified, and the ultraviolet absorption characteristics of the quantum dot material obtained vary with the amount of sulfur source added in step (2). DETAILED DESCRIPTION
[0046] The following is a detailed description of the present invention. The technical features described below are described based on representative embodiments and specific examples of the present invention, but the present invention is not limited to these embodiments and specific examples.
[0047] It should be noted that:
[0048] In this specification, the numerical range expressed using "a numerical value A to a numerical value B" means a range including the endpoints numerical values A and B.
[0049] In the present specification, the use of “substantially” or “essentially” means that the standard deviation from a theoretical model or theoretical data is within a range of 1%, preferably 0.9%, and more preferably 0.8%.
[0050] In this specification, unless otherwise specified, "%" means mass percentage.
[0051] In this specification, "room temperature" is used to refer to a temperature range of 23±2°C.
[0052] In this specification, when referring to the absorption peak position or the wavelength of light, the use of "nearby" means that the deviation of the position or the wavelength from the theoretical value is ±2 nm.
[0053] In this specification, the word "may" means both performing a certain process and not performing a certain process.
[0054] In this specification, the term "plurality" or "multiple" refers to a number greater than 2.
[0055] In this specification, the ultraviolet absorption characteristic peak / the wavelength corresponding to the peak described in the present invention refers to the (first) absorption peak that can be tested within the test range or the wavelength corresponding to the peak (scanning the wavelength from low to high), and such ultraviolet absorption characteristic peak is the main absorption peak considered in the art (e.g., the peak with the largest or larger peak area).
[0056] In this specification, unless otherwise specified, "quantum dot" and "quantum dot material" have equivalent physical and chemical meanings.
[0057] In the present specification, "optional" or "optionally" means that the event or situation described below may or may not occur, and the description includes cases where the event occurs and cases where it does not occur.
[0058] In this specification, the references to "some specific / preferred embodiments", "other specific / preferred embodiments", "embodiments", etc., mean that the specific elements (e.g., features, structures, properties and / or characteristics) described in connection with the embodiments are included in at least one embodiment described herein, and may or may not exist in other embodiments. In addition, it should be understood that the elements may be combined in various embodiments in any suitable manner.
[0059] The present invention mainly provides a preparation method of a zinc sulfide quantum dot material having a good absorption peak shape in the near-ultraviolet region and a zinc sulfide quantum dot material, which can meet the requirements of a spectrometer for near-ultraviolet absorption detection and endow the spectrometer with good detection or working capabilities in the 280-310nm band. The present invention is mainly based on the following insights:
[0060] It has been found that when synthesizing zinc sulfide quantum dot materials, when synthesizing quantum dots with light absorption characteristics in the near ultraviolet region, the prior art is not ideal in terms of the synthesis control process. Although attempts have been made to adjust the temperature and the type of ligand, the oily quantum dot materials that are finally obtained still cannot provide an absorption peak with a good peak shape in the near ultraviolet region. Further, the present invention attempts to improve the hot injection method, that is, by using a two-step method and combining temperature regulation to more accurately control the final quantum dot morphology, as a result, the ultraviolet absorption characteristic peak of the obtained zinc sulfide quantum dot material can be increased by 1 to 80 nm on the basis of the zinc sulfide quantum dot seed particles, thereby providing an absorption peak with a position controllable and good peak shape in the 231 to 310 nm band, and in particular, a zinc sulfide quantum dot material with a good peak shape in the 280 to 310 nm band can be obtained.
[0061] (Synthesis of quantum dots by thermal synthesis)
[0062] The zinc sulfide quantum dots of the present invention can be obtained by the two-step thermal synthesis method of the present invention.
[0063] Furthermore, there is no particular limitation on the specific implementation of the thermal synthesis method of the present invention, and examples thereof include the hot injection method or microfluidic synthesis method in the art.
[0064] Steps in seed synthesis
[0065] The seed synthesis step of the present invention is mainly obtained by mixing a sulfur source with a zinc precursor under heating.
[0066] The zinc precursor can be mainly formed by a zinc source, a ligand compound and an organic solvent.
[0067] In principle, the present invention has no particular limitation on the zinc source, and the zinc source commonly used in the art for preparing oil-soluble zinc sulfide quantum dot materials can be used. In some specific embodiments, the zinc source can be one or more of a zinc salt or a zinc oxide.
[0068] For zinc salts, in some preferred embodiments, organic or inorganic salts of zinc may be cited, such as zinc acetate or its hydrate, zinc perchlorate, zinc stearate, zinc citrate or its hydrate, etc.; for zinc oxides, zinc oxide may be cited. These zinc sources may be used directly or after being treated.
[0069] Further, in some preferred embodiments of the present invention, the zinc source of the present invention may be anhydrous zinc acetate or zinc oxide.
[0070] In principle, there is no particular restriction on the above-mentioned ligand compound. From the perspective of forming a quantum dot material with a suitable particle size, the ligand compound of the present invention may include aliphatic carboxylic acid compounds, preferably, aliphatic carboxylic acids having a carbon number of 10 or more, preferably 10 to 30, and more preferably 12 to 22, especially those (unsaturated) aliphatic carboxylic acids with a straight-chain structure. Specific examples include one or more of lauric acid, myristic acid, palmitic acid, stearic acid or oleic acid. From the perspective of forming a better peak shape in the 280 to 310 nm band and better controllability, the above-mentioned ligand of the present invention is preferably oleic acid.
[0071] As for the organic solvent for forming the zinc precursor, it is sufficient as long as it can dissolve the zinc source and the ligand compound to form a substantially uniform zinc precursor solution. Such an organic solvent can preferably be a non-ligand type solvent, which can include hydrocarbon solvents, ether solvents or nitrogen-containing solvents. More preferably, the organic solvent can be octadecene.
[0072] In principle, there is no particular restriction on the formation method of the zinc precursor. In some specific embodiments of the present invention, the zinc source and the ligand compound can be dissolved in the organic solvent. At this time, for the concentration of the zinc source, in some specific embodiments, it can be 0.5 mol / L or less (in terms of zinc element), preferably 0.01-0.4 mol / L, and more preferably 0.02-0.3 mol / L. If the concentration is too high, there may be concerns about poor controllability in some cases, and if the concentration is too low, there may be concerns about poor yield. In addition, for the amount of the ligand compound, in some preferred embodiments of the present invention, the ratio of the ligand compound to the zinc source (in terms of moles of zinc element) is greater than 1:1, preferably 5-2:1, for example, 4-2.5:1, etc. Among them, excess ligands can be beneficial to the generation and stabilization of subsequent quantum dot particles.
[0073] When forming the zinc precursor, other auxiliary means may be optionally used, which may include heating the system when necessary, for example, by heating the system above 140°C to increase the solubility of the zinc source. In addition, the system may be kept in a vacuum or inert gas protected state during the precursor formation.
[0074] Furthermore, the sulfur source is not particularly limited in principle, and may be simple sulfur, sulfur salts, or other sulfur-containing compounds.
[0075] In some specific embodiments, the sulfur source can be elemental sulfur, disulfide, thioacetamide, etc. More preferably, thioacetamide can be used as the sulfur source. Further, the sulfur source can be used in the form of a pure compound or in the form of a solution containing the sulfur source.
[0076] In some more preferred embodiments, the sulfur source can be used in the form of a solution in combination with a solvent.
[0077] Such a solvent may typically be an aliphatic amine compound, and in some preferred embodiments, may be an aliphatic primary amine having 8 to 18 carbon atoms, especially a primary amine having a straight chain structure. The ratio of the aliphatic amine compound to the sulfur source (in terms of moles of the S element) may be 3 to 8:1, preferably 4 to 7:1, in some specific embodiments of the present invention.
[0078] In principle, there is no particular limitation on other solvents that can be used, as long as they can dissolve the above components. Preferably, they can be the same solvents as those used to form the zinc precursor.
[0079] In addition, there is no particular limitation on other auxiliary means that can be used when forming a solution, and heating, inert environmental conditions, etc. can be provided according to actual needs.
[0080] Further, a first thermal synthesis step is performed.
[0081] Before mixing with the sulfur source, in some specific embodiments of the present invention, the zinc precursor solution can be maintained or cooled to a temperature (T1) below 95°C, for example, in the temperature range of 50-95°C or 70-90°C, and the sulfur source is added to form a mixed system with the zinc precursor solution. Since the reaction will be carried out quickly at this temperature to form zinc sulfide seeds. Therefore, preferably, after the sulfur source is (once) injected, the heating is stopped immediately and the system is cooled to room temperature.
[0082] As for temperature T1, this is related to the characteristics of the target seed particles. If it is too high, it may cause nucleation to be too fast and fail to obtain the ultraviolet absorption characteristics of the zinc sulfide quantum dot seed particles described below. If the temperature is low, it may also cause the nucleation rate to be too slow, resulting in too low process efficiency, poor operability and economy.
[0083] Furthermore, regarding the amount of the sulfur source and the zinc precursor, in some specific embodiments, the ratio of S:Zn is 0.01 to 0.6:1, such as 0.04:1, 0.18:1, 0.27:1, 0.51:1, etc., based on the moles of sulfur and zinc.
[0084] Furthermore, after obtaining the above-mentioned unpurified zinc sulfide quantum dot seed product system, the seeds are purified to obtain zinc sulfide quantum dot seed particles.
[0085] In principle, there is no particular limitation on the purification (separation) treatment that can be used. For example, a poor solvent may be added to precipitate the zinc sulfide quantum dot seed particles, thereby removing unreacted substances or impurities.
[0086] Purification can improve the growth of quantum dot materials in the subsequent secondary growth step and facilitate subsequent control. In principle, there is no particular restriction on the specific method of purifying zinc sulfide quantum dot seeds, such as precipitation, extraction or adsorption.
[0087] In some specific embodiments, the prepared zinc sulfide quantum dot seed stock solution is precipitated with ethanol and acetone solution and centrifuged to obtain purified zinc sulfide quantum dot seed particles.
[0088] In other specific embodiments, the prepared zinc sulfide quantum dot seed stock solution is added to a chloroform solution and mixed, and then a methanol solution is added and stirred evenly, and then allowed to stand for stratification, and the lower solution layer is removed. Preferably, the steps of adding chloroform solution and methanol solution and stirring and standing to remove the lower solution layer can be repeated multiple times until the quantum dot solution becomes a flocculent precipitate, and then centrifuged to obtain purified zinc sulfide quantum dot seed particles.
[0089] By performing the above-mentioned first thermal synthesis step and purification step, zinc sulfide quantum dot seed particles are finally obtained, and the seed particles have a characteristic ultraviolet absorption peak with a wavelength of 230 to 280 nm, preferably a characteristic ultraviolet absorption peak of 240 to 260 nm or 245 to 255 nm. In addition, in some preferred embodiments, such an absorption peak can generally have a half-peak width of less than 30 nm, preferably 22 to 28 nm.
[0090] (Secondary Growth Step)
[0091] In the synthesis route of the present invention, after the above-mentioned seed synthesis step, the purified zinc sulfide quantum dot seed particles can be mixed with additional zinc precursor solution and sulfur source to perform secondary growth and obtain the final zinc sulfide quantum dot material.
[0092] In some specific embodiments of the present invention, the secondary growth step of the present invention may include: preparation of an additional zinc precursor solution, preparation of an additional sulfur source, an injection step of zinc sulfide quantum dot seed particles, and a second thermal synthesis step.
[0093] The additional zinc precursor solution and the additional sulfur source may be prepared in the same manner as the zinc precursor solution and the sulfur source described above.
[0094] Furthermore, regarding the injection of zinc sulfide quantum dot seed particles, in some specific embodiments of the present invention, the injection of zinc sulfide quantum dot seed particles may be performed after the additional zinc precursor solution is heated to the temperature T2.
[0095] The temperature T2 is usually 30° C. to 200° C. higher than T1, and T2 may be above 120° C. Such a temperature is also conducive to the formation of quantum dot materials in the subsequent second thermal synthesis step.
[0096] Regarding the dosage of zinc sulfide quantum dot seed particles, in some specific embodiments, the added amount of zinc sulfide quantum dot seed particles is 5000-7000 OD, for example, 5500 OD, 6000 OD, 6500 OD, etc.
[0097] After the zinc sulfide quantum dot seed particles are added, a zinc precursor solution containing zinc sulfide quantum dot seed particles is formed, and then the second thermal synthesis step of the present invention is carried out at a temperature of T2. In some preferred embodiments of the present invention, the T2 may be 130 to 250°C; in some more preferred embodiments of the present invention, the T2 may be 200 to 250°C, for example, 220°C, 225°C, 230°C, 235°C, 240°C, 245°C, etc.
[0098] The second thermal synthesis step of the present invention allows the zinc sulfide quantum dot seed particles to continue growing on their surfaces.
[0099] Regarding the amounts of the sulfur source and the zinc precursor in the overall scheme (comprising the first thermal synthesis step and the second thermal synthesis step), in some specific embodiments, the molar ratio of Zn:S is 2.9:1 to 6.3:1, such as 2.9:1, 3:1, 4.5:1, etc., based on the moles of sulfur and zinc. In other specific embodiments, relative to the total molar number M of sulfur and zinc in the first thermal synthesis step, the total molar number of sulfur and zinc in the second thermal synthesis step is (8% to 21%)*M.
[0100] Further, in the second thermal synthesis step, the amount of the sulfur source and the zinc precursor, in some specific embodiments, the molar ratio of Zn:S is 1.1 to 4:1, preferably 1.2 to 3.5:1, and more preferably 1.3 to 3.1:1, based on the moles of sulfur and zinc. In other specific embodiments, the amount of the Zn precursor is 32 to 40% by volume, and the amount of the S source is 6 to 68% by volume, relative to the total volume of the sulfur source solution and the zinc precursor solution (100% by volume), wherein the solid content of Zn is 0.00411 to 0.06576 g / mL, such as 0.01644 g / mL, and the solid content of S is 0.000703 to 0.011248 g / mL, such as 0.002812 g / mL.
[0101] Regarding the order of adding the sulfur source and the zinc precursor, in some specific embodiments of the present invention, in the second thermal synthesis step, under the condition of maintaining the temperature T2 of the reaction system (zinc precursor solution containing zinc sulfide quantum dot seed particles), the above-mentioned additional sulfur source is gradually injected therein. Preferably, the sulfur source can be dripped in a dropwise manner. In some other specific embodiments, during the process of injecting the sulfur source, a new zinc precursor solution can also be added. For example, after injecting the sulfur source, a new zinc precursor solution is added, and then the sulfur source is added.
[0102] Under the reaction conditions, quantum dot particles continue to grow in the reaction system, and the ultraviolet absorption characteristics of the obtained quantum dot material can be controlled by controlling the amount and rate of addition of the sulfur source.
[0103] In some specific embodiments, the quantum dot material obtained in the above reaction process can be monitored in real time, and when the quantum dot material with the required ultraviolet absorption characteristics is obtained, the addition of the sulfur source and the heating are stopped.
[0104] Afterwards, the reaction system can be cooled to room temperature. In some preferred embodiments, the final quantum dot material can be purified and other treatments can be performed. The purification treatment can be carried out in accordance with existing techniques or experience in the field.
[0105] (Characteristics of quantum dot materials)
[0106] In the present invention, the wavelength corresponding to the ultraviolet absorption characteristic peak of the zinc sulfide quantum dot material obtained by the above scheme is 1 to 80 nm, preferably 5 to 70 nm, more preferably 10 to 60 nm, and particularly preferably 20 to 50 nm, compared with the wavelength corresponding to the ultraviolet absorption characteristic peak of the zinc sulfide quantum dot seed particles. Specifically, the zinc sulfide quantum dot material has an ultraviolet absorption characteristic peak with a wavelength of 231 to 310 nm. Preferably, the wavelength position of the ultraviolet absorption characteristic peak is 240 to 310 nm, 250 to 310 nm, or 255 to 310 nm. The half-peak width of such an ultraviolet absorption characteristic peak is less than 25 nm, preferably 14 to 22 nm.
[0107] In some specific embodiments of the present invention, the ultraviolet absorption characteristic peak (or absorption peak) is the first main absorption peak from long wavelength to short wavelength within the scanning range (scanning wavelength from low to high); in some other specific embodiments of the present invention, the ultraviolet absorption characteristic peak is the only main absorption peak within the scanning range (scanning wavelength from low to high).
[0108] For the quantum dot material of the present invention, its surface has a ligand, which is mainly or solely derived from the ligand compound used in the zinc precursor. In some preferred embodiments of the present invention, it can be an aliphatic carboxylic acid with a carbon number of more than 10, preferably 10 to 30, and more preferably 12 to 22, especially those (unsaturated) aliphatic carboxylic acids with a straight chain structure. More preferably, the ligand can be oleic acid.
[0109] In addition, the quantum dot material of the present invention may be further modified by ligand exchange or the like to satisfy the redispersibility in different systems or solvents.
[0110] (Optical Equipment)
[0111] Furthermore, the present invention provides an optical device based on the optical properties of quantum dots.
[0112] In some preferred embodiments of the present invention, the optical device may be a spectrometer or a filter device having high requirements on light absorption characteristics.
[0113] Such a spectrometer or filter includes or uses the quantum dot material prepared by the above method of the present invention.
[0114] For the spectrometer of the present invention, through the application of the quantum dot material of the present invention, it has a spectral capability or quantitative detection capability that meets the requirements in the ultraviolet band with a wavelength of 235 to 310 nm, especially in the near-ultraviolet band with a wavelength of 280 to 310 nm (the half-peak width is less than 25 nm, for example, 18 to 22 nm).
[0115] The spectrometer of the present invention may preferably be a miniature spectrometer or a portable spectrometer.
[0116] Example
[0117] The embodiments of the present invention are described in detail below with reference to the examples. If no specific conditions are specified in the examples, the reaction is carried out according to conventional conditions or conditions recommended by the manufacturer. If no manufacturer is specified for the reagents or instruments used, they are all conventional products that can be obtained commercially.
[0118] Example 1: Preparation of ZnS quantum dots with a UV absorption characteristic peak of 280 nm
[0119] (1) Preparation and purification of ZnS quantum dot seed particles:
[0120] 1a. Weigh Zn (zinc acetate) and place it in a reactor, and place oleic acid and ODE (octadecene) solution therein, wherein the molar ratio of Zn to oleic acid is 1:3.
[0121] 1b. The mixed system is stirred, evacuated, heated, and then cooled to 80° C. for standby use to obtain a Zn precursor solution.
[0122] 1c. Take another reactor and add thioacetamide and oleylamine solution and solvent ODE (octadecene), wherein the molar ratio of S to oleylamine is 1:6. Then evacuate the reactor, and then heat to 100° C. under nitrogen and normal pressure to prepare a S source.
[0123] 1d. Hot-inject the above-mentioned S source into the Zn precursor solution at 80°C, then stop heating and cool to room temperature.
[0124] 1e. The prepared ZnS quantum dot seed stock solution was purified with ethanol and acetone to obtain ZnS quantum dots, which were redissolved in ODE and tested for wavelength and concentration to obtain ZnS quantum dot seed particles with a UV absorption characteristic peak near 250 nm.
[0125] (2) Secondary growth of ZnS quantum dot materials:
[0126] 2a. Weigh Zn (zinc acetate) and place it in a reactor, and place oleic acid and ODE solution therein, wherein the molar ratio of Zn to oleic acid is 1:3.
[0127] 2b. The mixed system obtained in 2a above was stirred and evacuated, and then heated to 150° C., and then nitrogen was introduced and the temperature was raised to 240° C. to obtain a Zn precursor solution.
[0128] 2c. Take another reactor and add thioacetamide and oleylamine solution and solvent ODE (octadecene), wherein the molar ratio of S to oleylamine is 1:6. Then evacuate the reactor, and then raise the temperature to 100° C. under nitrogen and normal pressure to prepare a S source.
[0129] 2d. Inject the ZnS quantum dot seed particles with a UV absorption characteristic peak of 250 nm prepared in the above step (1) into the Zn precursor solution at 240°C, and then slowly add about 20 mL of S source, and aspirate the original solution for UV testing. After the growth wavelength reaches 280 nm, stop heating, cool and purify to obtain the secondary grown ZnS quantum dot material with a UV absorption characteristic peak of 280 nm.
[0130] Example 2: Preparation of ZnS quantum dots with a UV absorption characteristic peak of 285 nm
[0131] The steps are the same as those in Example 1, except that: the purification method in step 1e is adjusted as follows, and the volume of the S source added in step 2d is adjusted to 24 mL;
[0132] 1e. Add chloroform solution to the prepared ZnS quantum dot seed stock solution and mix, then add methanol solution and stir evenly, then let stand to separate layers, remove the lower solution layer, repeat several times until the quantum dot solution becomes a flocculent precipitate and then centrifuge, finally obtain ZnS quantum dots, redissolve in ODE, and perform wavelength and concentration tests to obtain ZnS quantum dot seed particles with a UV absorption characteristic peak near 250nm.
[0133] Example 3: Preparation of ZnS quantum dots with a UV absorption characteristic peak of 290 nm
[0134] The steps are consistent with those in Example 1, except that the volume of the S source added in step 2d is 30 mL.
[0135] Example 4: Preparation of ZnS quantum dots with a UV absorption characteristic peak of 295 nm
[0136] The steps are the same as those in Example 1, except that after the volume of the S source in step 2d reaches 30 mL, 2 mL of the Zn precursor is added, and then 10 mL of the S source is added dropwise.
[0137] Example 5: Preparation of ZnS quantum dots with a UV absorption characteristic peak of 300 nm
[0138] The steps are consistent with those of Example 4, with the only difference being that 2 mL of Zn precursor is added in step 2d, and the volume of the S source subsequently added is changed to 25 mL.
[0139] Example 6: Preparation of ZnS quantum dots with a UV absorption characteristic peak of 250 nm
[0140] The steps are consistent with Example 1, but the wavelength of the ultraviolet absorption characteristic peak of the ZnS quantum dot seed particles is adjusted to 230nm, and the temperature in step 2b is adjusted from 240°C to cooling to 130°C, and the volume of the S source added in step 2d is changed to 5mL.
[0141] Example 7: Preparation of ZnS quantum dots with a UV absorption characteristic peak of 310 nm
[0142] The steps are consistent with Example 1, except that the wavelength of the ultraviolet absorption characteristic peak of the ZnS quantum dot seed particles is adjusted to 275 nm, and the volume of the S source added in step 2d is changed to 20 mL, and then 4 mL of Zn precursor is added, and then 30 mL of S source is added dropwise.
[0143] Comparative Example 1: Preparation of ZnS quantum dots with a UV absorption characteristic peak of 300 without purifying the ZnS quantum dot seed particles
[0144] Except that the ZnS quantum dot seed particles are not purified, everything else is the same as Example 6.
[0145] like Figure 8 As shown, the peak shape of the characteristic ultraviolet absorption peak of the obtained ZnS quantum dot material deteriorates (with the continuous addition of the S source in step (2) , the center position of the peak shifts to the right, but the peak shape tends to deteriorate).
[0146] Comparative Example 2: a. Try to use a one-step method to prepare ZnS quantum dots with a UV absorption characteristic peak of 300 nm. a. Weigh Zn (zinc acetate) and place it in a reactor, and take oleic acid and ODE (octadecene) solution and place it therein, wherein the molar ratio of Zn to oleic acid is 1:3.
[0147] b. Stir the mixed system, evacuate the system, heat it, and then cool it to 80° C. for standby use to obtain a Zn precursor solution.
[0148] c. Take another reactor and add thioacetamide and oleylamine solution and solvent ODE (octadecene), wherein the molar ratio of S to oleylamine is 1:6. Then evacuate the reactor, and then heat to 100° C. under nitrogen and normal pressure to prepare the S source.
[0149] d. Hot-inject the above-mentioned S source into the Zn precursor at 80°C, and further increase the temperature to 240°C for reaction to obtain a ZnS stock solution system. During this process, the molar ratio of S to Zn in the S source and the Zn precursor is adjusted to be the same as the molar ratio of S to Zn in the final reaction system of step (2) in Example 5, and the reaction time is kept consistent with the total time used in Example 1.
[0150] e. The prepared ZnS quantum dot stock solution was purified with ethanol and acetone, and finally the ZnS quantum dot material was obtained, which was redissolved in ODE and tested for wavelength and concentration, but no sharp absorption peak was observed near 300 nm.
[0151] It should be noted that, although the technical solution of the present invention is introduced with specific examples, those skilled in the art will appreciate that the present invention should not be limited thereto.
[0152] The embodiments of the present invention have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and variations will be apparent to those of ordinary skill in the art without departing from the scope and spirit of the described embodiments. The selection of terms used herein is intended to best explain the principles of the embodiments, practical applications, or technical improvements in the market, or to enable other persons of ordinary skill in the art to understand the embodiments disclosed herein.
Claims
1. A method for preparing zinc sulfide quantum dot material, characterized in that: The method comprises The steps of seed synthesis and the steps of secondary growth, in, In the seed synthesis step, zinc sulfide quantum dot seed particles are obtained through a first thermal synthesis step and a purification step, and the zinc sulfide quantum dot seed particles have an ultraviolet absorption characteristic peak with a wavelength of 230 to 280 nm; the purification step is to purify the obtained zinc sulfide quantum dot seeds after the first thermal synthesis step is completed to obtain the zinc sulfide quantum dot seed particles; In the secondary growth step, the zinc sulfide quantum dot material is obtained through a second thermal synthesis step, and the temperature T2 of the second thermal synthesis step is above 120°C. The second thermal synthesis step includes mixing a sulfur source with a zinc precursor solution containing the zinc sulfide quantum dot seed particles. The absorption characteristic peak corresponding wavelength of the zinc sulfide quantum dot material prepared by the second growth step is increased by 1 to 80 nm compared with the absorption characteristic peak corresponding wavelength of the zinc sulfide quantum dot seed particles.
2. The method according to claim 1, characterized in that In the seed synthesis step, the first thermal synthesis step comprises: The sulfur source is mixed with the zinc precursor solution at a temperature T1 of 50 to 95°C.
3. The method according to claim 2, characterized in that In the first thermal synthesis step, the sulfur source is used in the form of a solution.
4. The method according to any one of claims 1 to 3, characterized in that: The surface of the zinc sulfide quantum dot seed particles includes aliphatic carboxylic acid ligands.
5. The method according to any one of claims 1 to 4, characterized in that: The temperature T2 of the second thermal synthesis step is 30° C. to 200° C. higher than T1, and T2 is 120° C. or higher.
6. The method according to any one of claims 1 to 5, characterized in that: In the secondary growth step, the temperature of the zinc precursor solution is adjusted to T2 and then the zinc sulfide quantum dot seed particles are injected therein to form a zinc precursor solution containing the zinc sulfide quantum dot seed particles.
7. The method according to any one of claims 1 to 6, characterized in that: In the second thermal synthesis step, the position of the characteristic ultraviolet absorption peak of the zinc sulfide quantum dot material finally obtained is regulated by gradually injecting a sulfur source into the zinc precursor solution containing the zinc sulfide quantum dot seed particles. Optionally, during the injection of the sulfur source, the zinc precursor solution is also added.
8. A zinc sulfide quantum dot material prepared by the method according to any one of claims 1 to 7, characterized in that: The zinc sulfide quantum dot material has an ultraviolet absorption characteristic peak with a wavelength of 280 to 310 nm; the half-peak width of the ultraviolet absorption characteristic peak is less than 25 nm; The surface of the zinc sulfide quantum dot material has aliphatic carboxylic acid ligands with 10 to 30 carbon atoms.
9. An optical device, characterized in that: The optical device uses or contains the zinc sulfide quantum dot material obtained according to any one of the methods of claims 1 to 7 or the zinc sulfide quantum dot material according to claim 8.
10. The optical device according to claim 9, which is a spectrometer or a filter device.
Citation Information
Patent Citations
Method for synthesizing zinc sulfide quantum dots by using oil amine
CN102030360A
Oil-soluble zinc sulfide quantum dot and preparation method thereof
CN108485648A
Deep ultraviolet nanometer material, preparation method thereof and optical component containing nanometer material
CN117106442A